Nature’s grip: Unveiling the architecture and proteomics of the adhesive organ of a hill stream catfish, Pterygoplichthys disjunctivus - Jitendra Kumar Sharma; Usha Kumari; Swati Mittal; Ajay Kumar Mittal (PLoS ONE, 2025)
Light microscopy, scanning electron microscopy, and proteomics analysis using high-resolution accurate mass spectrometry exhibit significant adaptive structural modifications and characteristic proteins in the adhesive organ (AO) of Pterygoplichthys disjunctivus, that could assist the adhesion of the fish to the substratum. The free surface of the epithelium of AO showed characteristic mound-like tubercles separated by deep furrows. These could enhance surface grip, and assist in creation of vacuum facilitating adhesion effectively. Spine-like unculi on the surface of the epithelium appear to assist clinging of the fish to the substratum as well as to scrape food particles for feeding. Taste buds located on the summit of mound-like tubercles could serve as adaptations to enhance their sensitivity in food selection and in environmental perception. Mucous and serous goblet cell secretions are believed to function as biological adhesives and protective surface lubricants. Proteomic analysis identified 285 differentially expressed proteins in the AO compared to those in the ventral and the dorsal skin. Out of these proteins in the AO, 80 proteins were significantly abundant. These were Periplakin, Desmoplakin, and Filamin A-like (adhesion related proteins); KRT8 and KRT19 (keratinization associated proteins); Myosin-7, Myosin light chain 13, and Tropomyosin 1 (proteins involved in cytoskeletal organization); and Apolipoprotein A1 and Complement Component 9 (proteins related to immune defense). Gene ontology analysis using Enrichr software revealed the enrichment of unique biological functions and pathways. This study provides a comprehensive understanding of the adaptive strategies that enable P. disjunctivus to thrive in turbulent hillstream environments. Additionally, the proteomic profile established in this study serves as a foundation for characterizing and comparing skin proteomes across teleost species.